Deadly Sins, True Lies of the Reform: Confronting the Complicit Silence - Delgado Menéndez, Maria Antonieta (2009)
This paper aims to study the main reasons that prevent law students and lawyers from contributing to the reform of Peruvian justice, also focusing on various reasons that should serve as a basis for them to commit themselves within the professional responsibility to contribute to the reform of justice in Peru. In the first part the impediments are developed, such as the silence that is complicit, the belief in what is foreign, the belief in the impossibility of change, the resistance to get involved in the public, the negative view about the reform, the loss of capacity for indignation and the belief that changes are few. After that, each of the factors explained is analyzed and the real reason behind each one is discovered, denying said impediments. Finally, the paper gives seven reasons that professionally commit lawyers graduated from the Pontificia Universidad Católica del Perú to contribute and work for a judicial reform for the benefit of society, among which are the recognition and professional level, positioning and level of credibility, the quality and variety of interventions, the knowledge and experience in the sector, the optimal relationship with the operators of justice, the ease of access to information and the importance of presence and commitment within the reform.